Investigation of Tr82 Region According to the Growth Stages of Rostow - KESGİNGÖ, Hayrettin and DİLEK, Serkan (Asian Journal of Economic Modelling, 2016)
Rostow tried to explain economic development levels by introducing five basic stages. These stages are Traditional Society, Transitional Society, Society at the Stage of takeoff, Society at the stage of Drive to Maturity and Society at Age of High Mass Consumption. By this way economic development of countries or regions can be understood and explained. TR82 Region consists of Kastamonu, Sinop and Çankırı Provinces. This region is trying to solve problems about economic growth and development. Our research aims to evaluate region’s economy by considering growth stages of Rostow. This study contributes in the existing literature by analysing TR82 region according to Rostow Growth stages method first.